Srednjeveška stavbna zgodovina kapele sv. Jakoba v Konjicah - Oter Gorenčič, Mija (Acta historiae artis Slovenica, 2023)
Based on the analysis of the already known and newly discovered archival sources, new realisations about medieval mural paintings, the keystones bearing the coats of arms, and the architectural elements of the Chapel of St James, the article presents a revised interpretation of this building’s medieval architectural history. The research conducted reveals that from the very outset, the Konjice Chapel was constructed as a four-bay confraternity chapel and that it was already vaulted in the final third of the 14th century. The coats of arms of the Counts of Cilli, the Lords of Wallsee, and, as suggested in this paper, the priest and later Archdeacon Jakob Dürr suggest a close association with the influential Confraternity that had its headquarters in the Chapel. Meanwhile, prosopographical studies indicate that members of these noble families were closely connected at the time of the Chapel’s construction.
Keywords: architectural history; architectural sculpture; Celjski; Chapel of St James; Count of Cilli; Dürr (rodbina); Dürr family; grbovni sklepniki; Great Confraternity of Our Beloved Lady of the Dravsko polje Plain; heraldic keystones; kapela sv. Jakoba; Lords of Wallsee; medieval architecture; medieval mural paintings; Parish Church of St George; Slovenske Konjice (Slovenia); Slovenske Konjice (Slovenija); srednjeveška arhitektura; srednjeveške stenske poslikave; stavbna plastika; stavbna zgodovina; velika Marijina bratovščina na Dravskem polju; Wallsee (rodbina); župnijska cerkev sv. Jurija